Matrix Metalloproteinase-9 as a Novel Player in Synaptic Plasticity and Schizophrenia - Lepeta, Katarzyna (Schizophr Bull, 2015)
Recent findings implicate alterations in glutamate signaling, leading to aberrant synaptic plasticity, in schizophrenia. Matrix metalloproteinase-9 (MMP-9) has been shown to regulate glutamate receptors, be regulated by glutamate at excitatory synapses, and modulate physiological and morphological synaptic plasticity. By means of functional gene polymorphism, gene responsiveness to antipsychotics and blood plasma levels MMP-9 has recently been implicated in schizophrenia. This commentary critically reviews these findings based on the hypothesis that MMP-9 contributes to pathological synaptic plasticity in schizophrenia.